Ambra1 modulates the sensitivity of mantle cell lymphoma to palbociclib by regulating cyclin D1 - Zhiping Jiang; Ao Zhang; Wenjia Wei; Shujun Li (Scientific Reports, 2023)
Abstract Mantle cell lymphoma (MCL) is a rare B-cell malignancy with a predominantly aggressive clinical course and poor prognosis. Abnormal expression of Ambra1 is closely related to the occurrence and development of various tumors. However, the role of Ambra1 in MCL remains unknown. Here, we performed both in vitro and in vivo experiments to investigate how Ambra1 regulates MCL progression and whether Ambra1 modulates the sensitivity of MCL cells to the CDK4/6 inhibitor palbociclib. We discovered that MCL cells had decreased levels of Ambra1 expression relative to normal B cells. Overexpression of Ambra1 in MCL cells inhibited autophagy, reduced cell proliferation, migration, and invasion, and decreased cyclin D1 level. While knockdown of Ambra1 reduced MCL cell sensitivity to CDK4/6 inhibitor palbociclib. Furthermore, overexpression of cyclin D1 lowered the sensitivity of MCL cells to palbociclib, enhanced cell proliferation, migration, invasion, and autophagy, and inhibited cell apoptosis. When Ambra1 expression was inhibited, the in vivo antitumor effects of palbociclib on MCL were reversed. Ambra1 expression was downregulated but cyclin D1 expression was upregulated in MCL samples, demonstrating a negative correlation between Ambra1 and cyclin D1. Our findings suggest a unique tumor suppressor function for Ambra1 in the development of MCL.